Hubungan Antara Perkembangan Sektor Keuangan dengan Volatilitas Ekonomi di Indonesia - Romi Mulyadi H. (Economic Journal of Emerging Markets, 2004)
The study is conducted to analyze the causal relationship between financial sector development and economic volatility in Indonesia during the period of 1983.2-2000.4. The study uses three kinds of variables as proxies to the financial sector development. Whereas in order to measure economic volatility, the study uses standard deviation of GDP growth derived from Generalized Autoregressive Conditional Heteroscedasticity model (GARCH).The causality test is done using Granger-causality test. If the estimated variables are not stationary, yet cointegrated, thus the causality test will be in Error Correction Model (ECM). If the estimated variables are neither stationary nor cointegrated, thus the causality test will use all variables in the ffirst difference. The result shows that there is a Granger-causality in the short run from financial development to the economic volatility when the ratio of broad money and the ratio of banking credit to GDP are used. Meanwhile, when the ratio of demand deposit to narrow money is used, there is no granger-causality relationship between financial sector development and economic volatility.Keywords: GARCH, financial sector development, economic volatility, granger causality.